Modified Oxford technique of colpopexy for the treatment of uterine and vaginal vault prolapse: a retrospective pilot cohort study - Devassy, Rajesh; Naem, Antoine; Krentel, Harald; De Wilde, Rudy Leon (Frontiers in Surgery, 2023)
Pelvic organ prolapse is a common health issue that affects 30.8% of women. Laparoscopic sacrocolpopexy and colpopectopexy are two of the most common procedures to restore the pelvic anatomy. Mesh application on the other hand carries an increased complications risk over the short and long terms. The aim of this study is to provide a basis for meshless sacrocolpopexy and colpopectopexy. This study is a retrospective cohort pilot study that analyzed the data of patients with a stage 2 or higher pelvic organ prolapse according to the pelvic organ prolapse quantification system and underwent the modified technique for sacrocolpopexy and colpopectopexy. Descriptive statistics were used to express the different variables. A total of 36 patients met the inclusion criteria and provided consent for the participation in this study. The majority of patients were postmenopausal. 22 out of 36 patients received a previous prolapse surgery. All patients presented with reducible vaginal lump. Dyspareunia and sexual dysfunction were the most commonly reported symptoms. The intraoperative complications rate was 0%. Only one patient had a postoperative persistent urinary retention that was managed medically. The use of a double-ended Mersilene suture for the modification of laparoscopic sacrocolpopexy and colpopectopexy seems to be a safe alternative to the mesh-based pelvic reconstructive surgeries with a very low rate of intraoperative complications and favorable follow up outcomes.